PENGARUH MEKANISME CORPORATE GOVERNANCE TERHADAP LUAS PENGUNGKAPAN MODAL INTELEKTUAL: STUDI PADA PERUSAHAAN SEKTOR PERBANKAN - Afifah Novita Hardiani; Ihyaul Ulum; Siti Zubaidah (Jurnal Reviu Akuntansi dan Keuangan, 2017)
The aim of this research is to examine the affect of corporate governance mechanism on disclosure of intellectual capital on the banking sector companies. 27 companies were taken as sampleson this research. The objective of this research is to prove the affect of corporate governancemechanism on disclosure of intellectual capital on the banking sector companies. The analyticalmethods used in this research are Partial Least Square (PLS) and test directly (direct effect).Results indicated that the variable of corporate governance was positively affect the disclosureof intellectual capital on the banking sector companies which means all information in companies were disclosed.Keywords: mekanisme corporate governance, intellectual capital disclosure